KEPEMIMPINAN BERBASIS KELUARGA DI DAYAH ACEH: IMPLIKASI TERHADAP KESEMPATAN SANTRI YANG KOMPETEN - Cut Irhamna (Jurnal Tarbiyah Almuslim, 2025)
This research aims to explore the implications of family-based leadership in Dayah institutions in Aceh and its impact on opportunities for competent santri to assume leadership roles. Using a qualitative approach with a case study design, the study involved interviews with administrators, teachers, and santri from several Dayah institutions. The findings reveal that family-based leadership models in Aceh Dayah tend to limit leadership opportunities for non-family members, particularly those with higher academic and leadership competencies. This results in a stagnation of leadership dynamics, limiting the professional growth and development of santri. Additionally, the findings highlight that the leadership selection process is often based on family lineage rather than merit, which leads to the perpetuation of family control over Dayah leadership roles. The research suggests the need for a more inclusive leadership selection process that prioritizes competence and potential, rather than familial ties, in order to foster the professional development of santri and improve the overall management of Islamic education in Dayah institutions. These findings contribute to the ongoing discourse on leadership in Islamic educational settings and emphasize the importance of merit-based leadership selection to enhance educational outcomes.